(untitled) (Faridpur Medical College Journal, 2018)
The incidence of genital tuberculosis varies widely with the social status of the patient and her environment. The incidence is about 1% amongst gynecological patients attending the outpatient department in the developing country. Genital TB may be asymptomatic and the majority of women are diagnosed during investigations of infertility. Genital system TB represents 15-20% of extrapulmonary TB and is usually asymptomatic affecting mainly young women in the reproductive age group. Here we presented a case of genital TB which was diagnosed during laparotomy. After confirmation of diagnosis by histopathology, the case was successfully managed by anti-tubercular therapy for 9 months. Faridpur Med. Coll. J. Jan 2018;13(1): 53-55